Integrating Theory and Practice: Strategies for Teaching Reading in English Language Classrooms - Kurniawati, Kadek Lina; Indrawati, Ni Putu Ayu Candra Nora (English Education Department STKIP Agama Hindu Singaraja, 2023)
This study investigates effective reading strategies in English as a Foreign Language (EFL) classrooms by bridging theoretical frameworks with practical instructional approaches. Drawing on a qualitative content analysis of seven peer-reviewed journal articles published between 2009 and 2025, the study identifies key strategies aligned with schema theory, metacognitive strategy instruction, and the Content and Language Integrated Learning (CLIL) approach. These strategies are categorized into three stages of reading instruction: pre-reading, during-reading, and post-reading. The findings highlight the importance of activating background knowledge, combining intensive and extensive reading practices, promoting reading strategy awareness, and integrating reading and writing in subject-based instruction. The study also addresses the instructional adaptations required in low-resource settings, emphasizing the need for teacher training and contextualized support. By connecting theoretical insights with real classroom practices, the research offers a comprehensive model for enhancing reading comprehension and fostering learner autonomy in EFL contexts.